 ## Proof of the Chain Rule to accompany Applied Calculus (3e)

Techniques of Differentiation Topic Summary
Review Exercises on Techniques
Index of Calculus Proofs
Student Home
Everything for Calculus
Epañol The Chain Rule

If the function $f$ has derivative $f'$ and the function $u$ has derivative $\frac{du}{dx}$, then the composite function $f(u)$ is differentiable, and

 $\frac{d}{dx} [f(u)] = f'(u) \frac{du}{dx}.$

Proof From the definition of the derivative,

$\frac{u(x+h) - u(x)}{h}\ \to u' (x)$ as $h \to 0.$

Thus,

$\frac{u(x+h) - u(x)}{h} - u'(x) \to 0$ as $h \to 0.$

If we take $v$ to be the quantity

$v = \frac{u(x+h) - u(x)}{h} - u' (x),$

then $v \to 0$ as $h \to 0.$ If we solve this equation for $u(x+h),$ we get

$u(x+h) = u(x) + (u'(x) + v)h$     ...   (I)

where $v \to 0$ as $h \to 0$

Now the same is true for $f:$ Take $w$ to be the quantity
$w = \matleft{\* \frac{f(y + k) - f(y)}{k} - f'(y), \quad \text{ if } k \neq 0! 0, \quad \text{ if } k = 0}$

(Note that $w$ is a function of $k$ that is defined for $k$ near, or equal to, $0$). Then

$f(y+k) = f(y) + (f'(y) + w)k$     ...   (II)

whether or not $k = 0,$ and where $w \to 0$ as $k \to 0.$

What we are after is the derivative of $f(u(x)).$ Thus we need to calculate the limit of

$\frac{f(u(x+h)) - f(u(x))}{h}$

First look at the numerator: $f(u(x+h)) - f(u(x)).$ If we use formula (I) to substitute for $u(x+h)$ we get

$f(u(x+h)) - f(u(x)) = f [u(x) + (u'(x) + v)h] - f(u(x))$     ...   (III)

Now we use formula (II) to rewrite $f [u(x) + (u' (x) + v)h]:$

$f [u(x) + (u'(x) + v)h] = f(u(x)) + (f'(u(x)) + w)(u'(x) + v)h$     ...   (IV)
(Take (II) and replace y with, $u(x)$ and $k$ with $(u'(x) + v)h )$

Note that, as $h \to 0$, so does the quantity
$k = (u'(x) + v)h$
in equation (IV), and therefore so does the quantity w by (II). (We will use this fact below.)

Subtracting $f(u(x))$ from both sides of (IV) gives

$f [u(x) + (u'(x) + v)h] - f(u(x)) = (f'(u(x)) + w)(u'(x) + v)h$     ...   (V)

Putting (III) and (V) together now gives

$f(u(x+h)) - f(u(x)) = (f'(u(x)) + w)(u'(x) + v)h$.

This is the numerator of the expression we are after. Dividing by $h$ gives

$\frac{f(u(x+h)) - f(u(x))}{h} = \frac{(f'(u(x)) + w)(u'(x) + v)h}{h} = (f'(u(x)) + w)(u'(x) + v)$  .

Now let $h \to 0$. Since both $v$ and $w \to 0$ (see above for the reason that $w \to 0$), we obtain
$\lim_{h \to 0} \frac{f(u(x+h)) - f(u(x))}{h} = f'(u(x)) u'(x)$,

which is the chain rule. 